Two-dimensional particle-in-cell simulation of electron heating effect in multiple hollow cathode trenches with curved boundary - Park, Heesung; Sakiyama, Yukinori; Lee, Hae June (Frontiers in Physics, 2023)
A particle-in-cell simulation is suitable for simulating capacitively coupled plasma devices because it calculates the trajectory of particles with arbitrary energy distributions and has the advantage of analyzing sheath dynamics precisely. Implementing the ghost grid method in the Poisson solver makes it possible to simulate a curved structure in the structured grids. The electron transport and heating mechanism are determined according to the two-dimensional (2D) sheath dynamics. The hollow cathode effect on electron transport was analyzed by varying the hole shape and gas pressure. The spatial distributions of electron density and temperature are influenced by the energy relaxation length of electrons, which is affected by the energy distribution function and gas pressure. As a result, a new electron heating mode appears in the 2D structure.